2022
DOI: 10.7759/cureus.23081
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Online Dissection Course on Lower Limb Anatomy During the COVID-19 Pandemic

Abstract: Introduction: The teaching of human anatomy, a medical subject that relies heavily on live teaching, teacher-student interactivity, and visuospatial skills, has suffered tremendously since the COVID-19 pandemic mandated the shutting down of medical institutions. The medical education fraternity was compelled to replace the traditional teaching method of hands-on cadaveric dissections (HOCDs) with online education to overcome this new challenge, but it came at the cost of reduced student engagement and lesser s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Overall, our findings confirmed that online teaching had its own characteristics that were more conducive to LOCS than offline teaching, but not to the development of HOCS. Also, in motor and attitude domains, it was discovered that it may not be as effective as traditional teaching, as it may reduce student concentration in the course [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our findings confirmed that online teaching had its own characteristics that were more conducive to LOCS than offline teaching, but not to the development of HOCS. Also, in motor and attitude domains, it was discovered that it may not be as effective as traditional teaching, as it may reduce student concentration in the course [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the rationale for doing These innovation rationales are interesting because they highlight concerns that might be addressed by digital education in the Indian context. Among the most frequently cited are the introduction of a new national curriculum [11,12], the need to reach remote areas [13,14], and the campus lockdowns imposed during the COVID pandemic [15][16][17][18]. Other rationales for exploring digital educational practices include catering to linguistic and cultural diversity [19], alleviating the general scarcity of health professionals [14], and cutting costs [20].…”
Section: Study Rationalesmentioning
confidence: 99%